Impact of Cataract Surgery on IOP and Ocular Structures in Normotensive Patients and Primary and Exfoliation Open-Angle Glaucoma Patients - Xirou V; Xirou T; Siganos C; Ntonti P; Georgakopoulos C; Stavrakas P; Makri OE; Kanakis M; Tsapardoni F; Fragkoulis I; Garnavou-Xirou C; Kozobolis V (Clinical Ophthalmology, 2023)
Vasiliki Xirou,1 Tina Xirou,1 Charalambos Siganos,2 Panagiota Ntonti,3 Constantinos Georgakopoulos,4 Panagiotis Stavrakas,4 Olga E Makri,4 Menelaos Kanakis,4 Foteini Tsapardoni,4 Ioannis Fragkoulis,4 Christina Garnavou-Xirou,1 Vassilios Kozobolis3– 5 1Ophthalmology Department, Hellenic Red Cross Hospital of Athens, Athens, Greece; 2Ophthalmology Department, University Hospital of Heraklion, Heraklion, Greece; 3Ophthalmology Department, University Hospital of Alexandroupolis, Alexandroupolis, Greece; 4Ophthalmology Department, University Hospital of Patras, Patras, Greece; 5Eye Institute of Thrace, Democritus University of Thrace, Alexandroupolis, GreeceCorrespondence: Vasiliki Xirou, Ophthalmology Department, Hellenic Red Cross Hospital of Athens, Athens, Greece, Email vxirou@yahoo.itPurpose: The aim of this study was to evaluate and compare the changes in Intraocular Pressure (IOP) and other ocular parameters: the Anterior Chamber Angle (ACA), Anterior Chamber Volume (ACV), and Anterior Chamber Depth (ACD) during phacoemulsification surgery in Greek patients with normotensive eyes and those with well-controlled Open-Angle Glaucoma (OAG). Additionally, parameters such as the Corneal Thickness (CCT), Axial Length (AL), Central Macular Thickness (CMT), and Retinal Nerve Fibre Layer (RNFL) were also examined.Patients and Methods: This was a prospective observational case–control study that included 50 phakic eyes, 25 normotensive (Group 1), and 25 with OAG: 15 Primary Open-Angle Glaucoma (POAG) and 10 Exfoliation Glaucoma (EXG) (Group 2). Ophthalmic assessment included IOP measurements, ocular biometry, and anterior and posterior segment optical coherence tomography evaluation of the aforementioned ocular parameters, prior and 6 months after phacoemulsification surgery.Results: At the 6 months post-operative review, a greater IOP reduction was recorded in eyes with OAG, in comparison to normotensive ones (5.3mmHg and 1.6 mmHg respectively). In addition, a significant but similar increase was recorded in the values of the ACA, ACV, and ACD of both groups between the pre- and the post-op period. Furthermore, the CCT and AL values remained unaltered. Finally, there was a non-statistically significant change in the mean CMT and the mean average RNFL of both groups.Conclusion: Eyes with OAG tend to undergo a greater reduction in IOP post-phacoemulsification surgery, in comparison to normotensive eyes. This reduction may not be solely attributed to ocular anatomical changes after phacoemulsification surgery but may also be due to the remodeling of the trabecular meshwork and the ciliary body. This may be especially true in the case of OAG eyes, which already start off with a compromised trabecular endothelium prior to surgery.Keywords: cataract surgery, open angle glaucoma, biometry, axial length, intraocular pressure, corneal pachymetry